2019
DOI: 10.1088/1748-9326/ab2a26
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of atmospheric air temperature and dew point temperature to extreme rainfall

Abstract: To understand the expected changes of extreme rainfalls due to climate change, the sensitivity of rainfall to surface temperature is often calculated. However, as surface temperatures may not be a good indicator of atmospheric moisture, an alternative is to use atmospheric temperatures, but the use of atmospheric temperatures lacks precedent. Using radiosonde atmospheric temperature data at a range of geopotential heights from 34 weather stations across Australia and its territories, we examine whether atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…This is consistent with Bui et al . (2019), who found consistent precipitation scaling with dewpoint temperature at the surface and in various layers above the surface, based on station and radiosonde data in Australia. Overall, we see that, while higher dewpoint temperatures are favourable for heavy and extreme rainfall, they do not represent a sufficient condition for these events.…”
Section: Environmental Characteristicsmentioning
confidence: 87%
“…This is consistent with Bui et al . (2019), who found consistent precipitation scaling with dewpoint temperature at the surface and in various layers above the surface, based on station and radiosonde data in Australia. Overall, we see that, while higher dewpoint temperatures are favourable for heavy and extreme rainfall, they do not represent a sufficient condition for these events.…”
Section: Environmental Characteristicsmentioning
confidence: 87%
“…Various alternatives to surface dry‐bulb temperature have been proposed. The use of atmospheric temperatures instead of surface temperatures has showed modest improvement (Ali & Mishra, 2017; Bui et al, 2019; Golroudbary et al, 2019). Alternatively, the relationship between atmospheric water vapor has also been examined (Neelin et al, 2009; Roderick et al, 2019; Schiro et al, 2016), resulting in sensitivities more consistent with climate model predictions of future rainfall intensification (Roderick et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both tropospheric air temperature and DPT were found to scale positively and closer to the C‐C rate than scaling with SAT (Ali & Mishra, 2017). Atmospheric air temperature and DPT were suggested as suitable nonstationary covariates for the scaling of extreme rainfall (Golroudbary et al, 2019) with DPT performing better than atmospheric air temperature (Bui et al, 2019). Surface DPT measurements taken prior to rainfall events have been used as a scaling covariate to find a 14% per degree dependency, approximately twice that of the C‐C relation (Lenderink et al, 2011), and in general are found to be more likely to result in positive scaling when compared to the use of SAT (Ali et al, 2018; Lenderink & van Meijgaard, 2010; Panthou et al, 2014; Park & Min, 2017; Wasko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%